Analisis Penerapan Fungsi Dua Tahap Pada Relay Proteksi Sbef Transformator 60 MVA Di Gardu Induk Tello 150 kV - Hamka, Akhsan; Arham, Muhammad; Rombe, Marten (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Power transformer protection systems require continuous optimization to ensure operational reliability and protection selectivity. This study analyzes the implementation of a two-stage Standby Earth Fault (SBEF) relay on a 60 MVA power transformer at the Tello 150 kV Substation to improve protection coordination. The methodology includes system simulation using ETAP 12.6.0 and validation through field testing. The results indicate that the two-stage SBEF configuration with a first-stage current setting of 86.6 A (TMS 0.097) and a second-stage setting (TMS 0.117) using a Long Time Inverse characteristic provides optimal protection coordination. Phase-to-ground fault simulations demonstrate selective relay operation, with feeder GFR operating at 512 ms, incoming GFR at 982 ms, first-stage SBEF at 5380 ms, and second-stage SBEF at 6490 ms. Field testing using a CMC 356 relay test set shows a maximum error of 2.02%, confirming strong agreement between theoretical calculations, simulations, and practical implementation.